VD_FINDINFO HC / 2010 / 377 vom 20. März 2010 - VD Tribunal cantonal (2010)
APPRÉCIATION DES PREUVES, CONSTATATION DES FAITS, MENACEDROIT PÉNAL, PÉRIODE D'ESSAI | 180 CP, 44 ch. 1 CP, 411 let. h CPP, 411 let. i CPP